2017
DOI: 10.1177/0258042x17716601
|View full text |Cite
|
Sign up to set email alerts
|

Pre and Post Disinvestment Performance Evaluation of Indian CPSEs

Abstract: The fact that government-owned firms are typically less proficient or at least less gainful than private owned firms is widely hypothesized. Therefore, the disinvestment policy aims at dropping the participation of the public sector in the economic actions of the country in order to support private sector. The research endeavour set out to empirically examine the financial and operating performance of 15 Central Public Sector Enterprises (CPSEs) disinvested in India through public share offering mode during 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The study revealed momentous augment in the overall operational effectiveness in relation to sales and net income [21]. On the other hand, profitability recital showed unimportant results [8].…”
Section: Literature Reviewmentioning
confidence: 83%
See 1 more Smart Citation
“…The study revealed momentous augment in the overall operational effectiveness in relation to sales and net income [21]. On the other hand, profitability recital showed unimportant results [8].…”
Section: Literature Reviewmentioning
confidence: 83%
“…The basic rule of disinvestment is to boost capital, encourage civic participation on a wider basis and to achieve improved marketplace answerability [7]. Thus, disinvestment seeks to ensure optimal use of nationalized capital and to boost industrious effectiveness of the CPSEs [8].…”
Section: Introductionmentioning
confidence: 99%
“…The study further observed that the reform measures adopted so far had a positive effect on the performance of CPSEs in India. Mandiratta and Bhalla (2017) investigated the monetary and working performance of fifteen CPSEs that were disinvested in India in the period 2003-2012. The sample of the study represented four cognate groups, i.e., the manufacturing, mining, energy, and service sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In India, privatization has been a part of government policy for almost more than 2 decades now, leaving enough time for academic researchers to generate a wide range of empirical studies examining the effect of divestment. As explained by Mandiratta and Bhalla (2017), most of the privatization literature in India presents a thorough view of Indian disinvestment policy, related concepts and various emerging issues. A few researchers have also examined the issues like post disinvestment financial performance and operating efficiency of privatized PSUs.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This method of divestiture persisted till the year 2004. Afterward, disinvestment through public offering/offer for sale gathered momentum, and has remained a trend (Mandiratta and Bhalla, 2017).…”
Section: Introductionmentioning
confidence: 99%